Influence of Slope, Drainage and Depth on Variability of the Soil Properties in Pediment Landform of Gaya District, Bihar - S.K. Reza; Sk. Md. Asif; Jyotibrata Chakraborty; Benukantha Dash; Mouli Pal; Monalisa Santra; Akriti Bhardwaj; F.H. Rahman (Journal of the Indian Society of Soil Science, 2025)
The pediment landform of the study area in Gaya, Bihar, experiences drought and erosion and hence, it is important to evaluate the influence of slope, drainage, and depth on the variation of soil properties as these can alter the nutrient distributions within a landform. The analysis of surface and sub-surface soil samples collected from 47 profiles across the landform indicated that most of the soil had pH in the alkaline range (4.7 to 9.9) with an increase in sub-surface layers. Soil particle size distribution, especially clay accumulation, was significantly influenced by slope and drainage and it had a significant influence on CEC, whereas sand had a negative effect. In general, soil organic carbon (SOC) content of the area was low, and the variation in SOC across the different layers highlighted how important surface soil is in the carbon cycle. Available N, P, B and Cu showed a comparable trend like SOC, while surface soil was rich in SOC, N and micronutrients. The results showed a direct correlation between depth and landscape parameters (drainage and slope) in determining the soil properties in the area and the thus necessitated of landscape features based soil managements.